Exploring the impact of sibling relationships on psychosocial well-being ‘The Ties that Bind’ - Theodorou, Nikoletta (2012)
The purpose of this dissertation is to explore individuals’ perceptions of the possible impact that their sibling relationships might have on their psychosocial well-being. In this study two female and two male students that no longer live with their siblings were asked about their perceptions, thoughts and feelings. Interpretative Phenomenological Analysis was used to analyze the data and the researcher’s position was taken into consideration. Through the analysis three main themes emerged. These concerned the satisfaction that individuals gain from their relationships with their siblings, the protective nature of sibling relationships and the negative impact that the relationship might have on the individual. Analysis showed that individuals perceived an indirect link between the quality of their sibling relationships and their emotional well-being. In all, the participants considered the relationship significant to securing a sense of wellness and the very nature of the sibling bond was considered a determining factor. The main themes that emerged are to be discussed in relation to the existing literature. A lack of literature on the subject of sibling relationships in adulthood has been considered an area of concern. Finally, my aim is to gain a better understanding of the sibling relationships and their impact on the individual in adult life.